2017
DOI: 10.3892/ijo.2017.4015
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor microRNA-34a inhibits cell migration and invasion by targeting MMP-2/MMP-9/FNDC3B in esophageal squamous cell carcinoma

Abstract: MicroRNAs (miRNAs) are a large family of small, non-coding RNAs that play a pivotal role in tumorigenesis. miR‑34a, which is a member of the miR-34 family, is a downstream target of p53. Increasing evidence shows that miR-34a dysregulation may contribute to tumor development and progression in numerous cancers, including esophageal squamous cell carcinoma (ESCC). However, the mechanism of miR-34a in the regulation of ESCC cells need to be further elucidated because of the complex regulative network of miRNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 59 publications
5
40
0
Order By: Relevance
“…MMP2 was also found to be implicated in the proliferation of pancreatic and breast cancer cells (38). MMP2 can be targeted by several other microRNAs, such as miR-29b (39) and miR-34a (40), and it was herein verified that miR-93 directly targets MMP2 and plays an important role in NP cells.…”
Section: Discussionsupporting
confidence: 57%
“…MMP2 was also found to be implicated in the proliferation of pancreatic and breast cancer cells (38). MMP2 can be targeted by several other microRNAs, such as miR-29b (39) and miR-34a (40), and it was herein verified that miR-93 directly targets MMP2 and plays an important role in NP cells.…”
Section: Discussionsupporting
confidence: 57%
“…Qi Zhang et al reported that MMP2, HEY1 and HES1 together regulate the migration of adipose-derived stem cells and chondrocytes in a coculture system [51]. In tumor studies, MMPs induced tumor invasion and distant metastasis in a variety of tumors, such as breast cancer [52], osteosarcoma [53], endometrial cancer [54], and esophageal squamous cell carcinoma [55]. Therefore, we also studied the correlation between HEY1 and MMPs.…”
Section: Discussionmentioning
confidence: 92%
“…44 The effects of microRNAs on matrix metalloproteinases as well as fibronectin type III domain containing 3B expression levels have been studied in the past. 45 In this study, we found that introduction of miR-34a or knockdown of LGR4 can inhibit the expression level of MMP2, which has been shown to be responsible for the migration and invasion of many kinds of tumors. This is the first study to establish a possible causal relationship between LGR4 and expression of MMP2.…”
Section: Discussionmentioning
confidence: 73%